HuiShangGPT in the discussion on the trend of seismicity?. - Jing Huang; Shi Chen; Zhongliang Wu (Earthquake Science, 2025)
Given the complexity of earthquake forecast and the current limitations in the application of artificial intelligence (AI), we propose a conceptual framework for a novel AI system, HuiShangGPT, intended to act as an expert in discussion on the trend of seismicity. This system, still in the conceptual stage, aims to integrate AI into the empirical approaches traditionally used in earthquake forecasting. The proposed HuiShangGPT system would not only assist in the comprehensive analysis of seismic data but also contribute to the expert panel discussions, enhancing the decision-making process. We outline the envisioned functionalities and potential benefits of such a system, while acknowledging the technical and practical challenges that need to be addressed for its future implementation.